Effects of LaF3/CeF3 on the friction transfer of PTFE-based composites. (September 2021) - Xie, Ting; Shi, Yaru
Abstract: The friction transfer of polytetrafluoroethylene (PTFE) composites is closely related to their tribological performances. To clarify the effects of LaF3 /CeF3 on the friction transfer of PTFE-based composites, the transfer film thickness and coverage were investigated under different loads or speeds. The results show that the addition of LaF3 /CeF3 can decrease the transfer film thickness and increase the transfer film coverage to form a thin and uniform transfer film, and the co-filling of LaF3 and CeF3 is better in promoting friction transfer of PTFE-based composites than single addition of LaF3 or CeF3 . The correlation between transfer film and tribological properties was also analyzed, which indicates that the friction transfer is beneficial for improving the tribological properties of PTFE composites. Highlights: Effects of LaF3 /CeF3 contents, applied loads and sliding speeds on the friction transfer of PTFE-based composites. Relations between the transfer film thickness, coverage, and the tribological performances of the PTFE-based composites. LaF3 /CeF3 can delay PTFE composites degradation and stabilize transfer film to promote friction transfer. The co-filling of LaF3 and CeF3 can promote friction transfer of PTFE composites better than addition LaF3 or CeF3 only.